Future Perspective to Green Chemistry: A Review: Strategies for Environmentally Friendly Chemical Synthesis (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Green Chemistry is defined as environmentally benign chemistry. The synthetic schemes are designed in such a way that there is least pollution to the environment. As on today, maximum pollution to the environment is caused by numerous chemical industries. The cost involved in the disposal of the waste products is also enormous. Therefore, attempts have been made to design synthesis for manufacturing processes in such a way that the waste products are at minimum, they have no effect on the environment and their disposal is convenient. For carrying out reactions it is necessary that the starting materials, solvents and catalysts should be carefully chosen. For example Benzene (C6H6) as a solvent must be avoided at any cost since it is carcinogenic in nature. If possible, it is best to carry out reactions in the aqueous phase. With this view in mind, synthesis methods should be designed in such a way that the starting materials are consumed to the maximum extant in the final product. The reaction should also not generate any toxic by-products.